ANALISIS PELAKSANAAN EVALUASI PEMBELAJARAN OLEH GURU DI SMA NEGERI 1 KECAMATAN KUBU KABUPATEN ROKAN HILIR - Mira Ulfa Joza; Caska Caska; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTSMA Negeri 1 sub-district is the stronghold of one of the schools that are inRokan Hilir . To determine the success learning conducted in an educationalinstitution would require evaluation . The existence of an evaluation is deemedimportant in education . The purpose of the study was to determine the evaluationof learning by the teacher in SMA Negeri 1 Kubu Sub Rokan Hilir . Thepopulation in this study was the teacher of SMA Negeri 1 Rokan Hilir Subdistrictfaction consisting of thirty- six ( 36 ) teachers with sampling using a samplingtechnique that is saturated sampling technique used when all members of thepopulation as a sample . The technique of collecting data using questionnairesand documentation . techniques of data analysis using descriptive methods . Theresults showed that the evaluation of learning by the teacher in SMA Negeri 1Kubu Sub Rokan Hilir 52.78% teachers in the criteria of " good " and 47.22%teachers who are on the criterion of "Very Good " . It can be seen in the abilityand expertise of the teachers at the time of the evaluation of learning that hasbeen noticed and understood education and evaluation procedures can alsointerpret the results of the evaluations are then followed up to obtain a moreoptimal learning .Keywords : Principles of assessment, assessment techniques, evaluation oflearning